PELATIHAN DESAIN LOGO DIGITAL UMKM BERBASIS CANVA BINAAN YAYASAN GENGGAM TANGAN INDONESIA - Wanda, Sulistianto Sutrisno; Marlinda, Linda; Gata, Windu (Universitas Pattimura, 2026)
Limitations in design skills and costs are obstacles for MSMEs to create an attractive visual identity or branding. Community service aims to provide an alternative solution to the problems faced by MSMEs under the auspices of the Indonesian Hands Foundation regarding their business logos through training using Canva-based digital applications. The activity implementation method includes the following stages: preparation, implementation with the learning by doing method (lectures, demonstrations, and direct practice), and activity evaluation. The activity was implemented on Saturday, September 20, 2025, at Nusa Mandiri Jatiwaringin University. Of the 20 training participants, the questionnaire results showed high participant enthusiasm. The results of the questionnaire analysis, participants of productive age (35-50 years) and the elderly (> 50 years) were the majority. The results showed a level of satisfaction with an average perception of committee services of 90.47% and the usefulness of the activity results of 91.69%. Real solutions were generated from this training for the participants, increased skills in utilizing science and technology, and the participants' confidence to be more enthusiastic about promoting their businesses